EFFECT OF ZINC SALTS FORTIFICATION ON NITROGEN MATERIALS AND RHEOLOGICAL CHARACTERISTICA OF SOFT WHITE IRAQI CHEESE - & et al., Salih (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study aims to investigate  the effect of the fortification of soft white Iraqi cheese with some zinc salts at different levels include 100 and 200 mg.kgˉ¹ from zinc sulphate and zinc acetate, on Nitrogen materials and some rheological properties of the soft white cheese during the storage for 14 days. The results indicated that there was no significant effects for cheese fortification with  zinc salts on the percentage of Nitrogen materials during all storage periods. There was non-significant increase the nitrogen materials in the cheese of the control treatment in comparison to the zinc fortified treatments.  The results indicate a significant decrease in the values of cheese brightness of the fortified treatments. Also, zinc fortification caused a significant increase in the value of cheese compaction a compare to the control treatment.